Anatomical Variants of Deviated Nasal Septum and Its Association with Maxillary Sinus Volume - Khatun, Sanzida; Timsinha, Sidarth; Gautam, Mahesh; Khanal, Tekendra (Birat Journal of Health Sciences, 2025)
Introduction: Deviated Nasal Septum (DNS) is a common anatomical variation of the nasal septum that can significantly impact nasal airflow, sinus ventilation, and mucociliary clearance. Studies have demonstrated a potential association between DNS types and the volume of the maxillary sinus.There is limited evidence exploring the prevalence of Mladina’s DNS types and their association with demographic factors such as age and gender, as well as anatomical features like maxillary sinus volume in context of Nepal. Objectives: This study aims to determine the prevalence of various DNS types based on Mladina’s classification and evaluate the association of DNS with gender, age and maxillary sinus volume. Methodology: A cross-sectional, descriptive study was conducted in 222 patients whose Computerized Tomographic (CT) scans were evaluated to obtain the maxillary sinus dimensions and to find the presence of DNS, among which 110 patients had DNS. Demographic data were collected to acquire the information about age, and gender and CT scans of the paranasal sinuses were used to evaluate DNS types based on Mladina’s classification and Maxillary sinus volume using volumetric software. Results: Out of 222 patients, DNS was found in 110 (49.5%) subjects. The prevalence of DNS was 67 (57.3%) among total (117) males and 43 (41%) among total (105) females had DNS. Among 110 subjects with DNS, type 2 was the most common type which was present in 37 (33.6%) subjects; followed by type 5 which had 31 (28.2%) subjects and type 1 with 13 (11.8%) subjects. Out of 110 subjects with DNS, 55 (50.0%) had their nasal septum deviated to the right side; 46 (41.8%) had deviation to left side; 9 (8.2%) patients with type 4 (S-shaped) DNS were included in bilateral DNS group. No significant relation was found between maxillary sinus volume and various DNS literalities. Conclusion: This research emphasizes that DNS is a widespread anatomical variation, with type 2 and type 5 being the most frequent as per Mladina’s classification. The occurrence of DNS was observed to be greater in males and in younger people. No significant relationship was found between laterality of DNS and the volume of the maxillary sinus.